Differential Prescribing of Opioid Analgesics According to Physician Specialty for Medicaid Patients with Chronic Noncancer Pain Diagnoses. (2014) - Ringwalt, Chris; Gugelmann, Hallam; Garrettson, Mariana; Dasgupta, Nabarun; Chung, Arlene E; Proescholdbell, Scott K; Skinner, Asheley Cockrell
Abstract : BACKGROUND: Despite >20 years of studies investigating the characteristics of patients seeking or receiving opioid analgesics, research characterizing factors associated with physicians' opioid prescribing practices has been inconclusive, and the role of practitioner specialty in opioid prescribing practices remains largely unknown. OBJECTIVE: To examine the relationships between physicians' and other providers' primary specialties and their opioid prescribing practices among patients with chronic noncancer pain (CNCP). METHODS: Prescriptions for opioids filled by 81, 459 Medicaid patients with CNCP in North Carolina (USA), 18 to 64 years of age, enrolled at any point during a one-year study period were examined. χ 2 statistics were used to examine bivariate differences in prescribing practices according to specialty. For multivariable analyses, maximum-likelihood logistic regression models were used to examine the effect of specialty on prescribing practices, controlling for patients' pain diagnoses and demographic characteristics. RESULTS: Of prescriptions filled by patients with CNCP, who constituted 6.4% of the total sample of 1.28 million individuals, 12.0% were for opioids. General practitioner/family medicine specialists and internists were least likely to prescribe opioids, and orthopedists were most likely. Across specialties, men were more likely to receive opioids than women, as were white individuals relative to other races/ethnicities. In multivariate analyses, all specialties except internal medicine had higher odds of prescribing an opioid than general practitioners: orthopedists, OR 7.1 (95% CI 6.7 to 7.5); dentists, OR 3.5 (95% CI 3.3 to 3.6); and emergency medicine physicians, OR 2.7 (95% CI 2.6 to 2.8). CONCLUSIONS: Significant differences in opioid prescribing practices across prescriber specialties may be reflective of differing norms concerning the appropriateness of opioids for the control of chronic pain. If so, sharing these norms across specialties may improve the care of patients with CNCP.